Mengurangi Durasi Pelaksanaan Proyek Dengan Menggunakan Metode Time Cost Trade Off - Muhammad Rizal Hermawan; Ahmad Ridwan; Suwarno Suwarno (Faculty of Engineering, Kadiri University, 2021)
Construction project management is one of the things that affect the smooth work of construction projects. Time and cost become benchmarks in the success of a project. In the construction project Bhayangkara Nganjuk hospital indicated experiencing delays caused by unse endorsive weather conditions. The delay will have an impact on the costs that will be incurred. The purpose of this research is to accelerate the time on the project by using the time cost trade off method. Development work includes IGD room work, Pharmaceutical Installation, Laboratory and Inpatiation Room. The data used in the form of Time schedule and budget plan costs obtained from the implementing contractor. From the data, analysis is carried out in the form of determination of relationships between jobs, determination of critical pathways, and acceleration analysis by applying a work shift system. The relationship between jobs is illustrated through the Microsoft Project. The results of the study obtained a total cost after acceleration of Rp. 3,873,505,632.00 the value was more expensive 11.25% than the normal cost of the project of Rp 3,481,698,000.00. With an accelerated duration of 125 days or 25.71% faster than the normal duration of the project of 180 days. So that from these results, it can be used as a reference in the implementation of the project regarding work hours that can be applied as well as the cost of the project and the duration of acceleration required.